Child Physical Abuse Fundamentals in the Child Abuse Pediatrics Curriculum for Physicians (CAP-CuP) - Katie L. Johnson; Emily C. B. Brown; Caitlin E. Crumm (MedEdPORTAL)
Introduction Child abuse is a highly prevalent yet undertaught condition in medical education. Many physicians feel underprepared to navigate conversations about mandatory reporting. Methods We developed an interactive module for teaching pediatric clinicians about sentinel injuries and mandatory reporting. We evaluated the content by seeking qualitative and quantitative feedback from a large audience at a pediatric continuing medical education (CME) conference and then studied its educational impact using a pre- and postmodule assessment with residents from three specialties. Based upon audience and expert feedback, the content was then divided into two parts, with an expanded section on disproportionality in part one and popcorn-style role-play in part two. Results In the CME audience, 98% of participants (85 of 87) rated the content and presentation skills as excellent or very good. In the resident presentations, there were 34 resident participants from three specialties: 24 from a combined audience of pediatric and emergency medicine residents and 10 from an audience of family medicine residents. Median confidence level increased in the pediatric and emergency medicine audience from 4 to 7 and in the family medicine audience from 5 to 7 on a 10-point scale. The median knowledge scores increased in both groups as well, from 75% to 100% and 25% to 100%, respectively. Discussion This child physical abuse fundamentals module has been presented to a wide range of physician audiences with positive qualitative and quantitative feedback. It is offered here in an expanded two-part workshop that allows for intentional practice of the information taught.